COMPARATIVE ANALYSIS OF THE FINANCIAL PERFORMANCE OF AUTOMOTIVE SUB-SECTOR MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE (IDX) FOR THE PERIOD 2018-2021 - Adi Wijaya; Sri Hermuningsih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to test and analyze